2017
DOI: 10.2106/jbjs.16.00692
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Visits Following Elective Total Hip and Knee Replacement Surgery: Identifying Gaps in Continuity of Care

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 27 publications
3
56
1
Order By: Relevance
“…1,8,9 Specifically for ED visits after elective procedures, Finnegan et al evaluated patients who underwent total hip and knee arthroplasties. 10 They found that having Medicaid as primary insurance was statistically significantly associated with postoperative ED visits. Medicare was also a risk factor for ED visits compared to private insurance.…”
Section: Discussionmentioning
confidence: 99%
“…1,8,9 Specifically for ED visits after elective procedures, Finnegan et al evaluated patients who underwent total hip and knee arthroplasties. 10 They found that having Medicaid as primary insurance was statistically significantly associated with postoperative ED visits. Medicare was also a risk factor for ED visits compared to private insurance.…”
Section: Discussionmentioning
confidence: 99%
“…Findings regarding median household income were mixed across studies. Among the four studies using this SEDH, two demonstrated signi cant associations between median household income and emergency care indicators (52,56) and the other two did not. (50, 55) (See Additional le 4)…”
Section: Incomementioning
confidence: 99%
“…To measure income differences, four studies that used this SEDH used median income household (divided into quartiles or thirds) (50,52,55,56) and one used presence versus absence of a reportable income. (59) (It re ects the ability to reach and to pay).…”
Section: Incomementioning
confidence: 99%
See 1 more Smart Citation
“…(1) In a retrospective database study of 152,783 patients undergoing major joint replacements, 8883 (5.81%) of patients returned to the ED within 30 days, more common than 30-day readmissions of 5229 (3.42%), and pain was the most frequent single diagnosis at 25.75%. (2) Not uncommonly, patients return to a non-index hospital, which is not the hospital where surgery was performed originally. (3) The costs in such cases are higher, (4) as is the mortality.…”
Section: Introductionmentioning
confidence: 99%